Motivasi Petani Terhadap Peremajaan Tanaman Kelapa Sawit di Kecamatan Sungai Bahar Kabupaten Muaro Jambi - Siti Kurniasih; Fidi Kaseta Pratama; Arsyad Lubis; Endy Effran (Jurnal MeA (Media Agribisnis), 2022)
Motivation as a form of encouragement that arises from farmers both from outside and inside towards oil palm rejuvenation which encourages farmers  to do rejuvenation and those who have not done rejuvenation in order to improve    agricultural development through increasing the productivity of oil palm plants. This study aimed to: 1) To describe the condition of oil palm rejuvenation in Sungai Bahar Sub-district, Muaro Jambi Regency, 2) To find out the difference in motivation between farmers who had done rejuvenation and farmers who had not yet done oil palm rejuvenation in Sungai Bahar District, Muaro Jambi Regency. This research was carried out from July to August 2021 in Sungai Bahar District, Muaro Jambi Regency intentionally (purposively). The data used were primary data    and secondary data. The population in this study were oil palm farmers in Sungai Bahar District. The sampling technique in this study used double sampling, namely  random sampling and quota sampling. The number of sample farmers were 60  farmers with the distribution of 30 farmers who had not yet done oil palm rejuvenation in Suka Makmur and Marga Mulya villages and 30 farmers who had  done oil palm rejuvenation in Suka Makmur and Marga Mulya villages. While the data analysis used was descriptive analysis and quantitative analysis using the Mann Withney test. The results showed that: 1) Rejuvenation of conventional techniques in Sungai Bahar District using BPDPKS funding sources began in 2018. There were two farmer groups that received rejuvenation funding from BPDPKS in Sungai Bahar District, namely KUD Sari Makmur which was established in 2012 and Gapoktan Rambutan which was established in 2017. 2) The intrinsic motivation of          farmers who had not yet replanted was in the low category, i.e 39%, where debt wdas an obstacle to replanting oil palm plantations, on the external side, farmers who  had replanted were in the high category 63.4 %, as well as those who had not yet done rejuvenation classified in the high category, i.e. 62.6%.